CAUSES AND OUTCOMES OF PATIENTS ADMITTED TO THE INTENSIVE CARE UNIT WITH SYSTEMIC LUPUS ERYTHEMATOSUS: Systemic Lupus Erythematosus - Rashid, Dr Naveed Haroon; Khan, Maria Ali; Mahmood, Salman Bin; Aziz, Muhammad; Awan, Safia; Zubairi, Ali Bin Sarwar (Pakistan Armed Forces Medical Journal, 2018)
Objective: To identify the causes and outcome of patients admitted with systemic lupus erythmatosus (SLE)requiring intensive care unit care in a tertiary care hospital.Study Design: Retrospective record review study.Place of Duration of Study: Aga Khan University Hospital, 15 years from Jan 2001 to Dec 2015.Material and Methods: Medical record of past fifteen years (from 2001 till December 2015) was reviewed for alladult patients (age .16) admitted to intensive care unit with SLE. At the time of ICU admission patients wereevaluated for demographics characteristics, clinical and laboratory parameters, length of ICU stay, AcutePhysiology and Chronic Health Evaluation II (APACHE II) score and mortality.Results: During the study period, 58 patients were admitted to ICU; 47 (81%) were females and 11 (19%) weremales. Out of them 42 (72%) patients died, predominantly with septic shock. The mean age was 36.1 } 13.3 years.The main reason for ICU admission was respiratory (74%), neurological (50%), renal (18.9%), and cardiogenic(15.5%). Patients who had septic shock and multiorgan dysfunction syndrome had a higher mortality.Conclusion: Patients with higher APACHE II score, septic shock and multiorgan dysfunction syndrome at thetime of admission in ICU had a higher mortality.